Profile of Fatal Head Injury Cases Autopsied at District Governament Hospital Mortuary - Ashokkumar Rajaput; Kumar H; Faisal Nasim Gilani; Eshwar S Goudar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background and Objectives: the study of profile of skull fractures is important as head being the most exposed and prominent part of body; it becomes most susceptible to injuries, as a result of criminal violence or accident. The present study was taken up to know the incidence of head injuries, age relationship,sex relationship, agent causing skull fractures, common skull bone fractures. Methodology: data in the current study was collected from the autopsy reports and from police inquest of all fatal skull fractures from the period of june 2012 to may 2014 irrespective of age and sex with history of death due to head injuries brought for postmortem examination to the department of forensic medicine & toxicology, al-ameen medical college mortuary and district hospital mortuary, bijapur between june 2012 to may 2014.Results: most common circumstance causing skull fractures are road traffic accidents in 77 cases (81.94 %). Male preponderance over females noted in this study with males constituting 80 cases (85.10 %) and females 14 cases (14.89 %). The most common age group affected was 21-30 years. Blunt force is the most common agent causing the skull fracture in 90 cases (95.74 %) and least is sharp in 4 cases (4.25 %). Among skull fracture comminuted fracture were seen in 46 cases (48.93%) , linear fracture in 38 cases (40.42%), depressed fracture in 8cases (8.5%) and sutural fracture in 1 case and gutter fracture in 1 case (1.06%) respectively. Temporal bone was the commonest bone fracture in 17 cases (18.08%). Conclusion: the study had concluded that incidence of skull fractures were common at the age group of 21-30 years, with male predominance, most common cases were those of RTA, cause of death that were given in majority of cases was that of Head injury as a consequence of injuries sustained.